Comparison of hypothermic and normothermic cardiopulmonary bypass in patients undergoing coronary artery bypass graft surgery - Amaç, Bişar; Engin, Mesut; As, Ahmet Kağan; Abanoz, Mustafa; Yavuz, Şenol (The European Research Journal, 2025)
Objectives: Coronary artery bypass graft (CABG) surgery operations accompanied by cardiopulmonary bypass (CPB) are the most prominent treatment options. One of the basic application principles of the CPB system is the protection of vital organs by reducing metabolic rate and oxygen consumption with hypothermia. In this study, we aimed to investigate the effects of normothermia and hypothermia applications on clinical outcomes in CABG operations performed with CPB. Methods: This single-center study was planned retrospectively. Patients who underwent isolated CABG operation with CPB at Şanlıurfa Mehmet Akif İnan Training and Research Hospital between January 01, 2020, and January 01, 2022, were included. A total of 120 patients, 60 of whom underwent hypothermic and 60 normothermic cardiac bypass, were included in the study after applying the exclusion criteria. Results: There was no difference between the groups in terms of age, gender, diabetes mellitus, hypertension, left ventricular ejection fraction, and body surface area characteristics (P>0.05). In the normothermia group, urea, creatinine, direct bilirubin, and lactate levels were significantly higher in the first postoperative day blood values (P=0.003, P=0.04, P=0.028, P=0.005, and P